Pengaruh Kualitas Pelayanan Dan Perceived Value Terhadap Loyalitas Pelanggan Katering Butik Tumpeng Di Kota Depok - Munawaroh, Wildatum; Irvawan, Robby (JAMBIS : Jurnal Administrasi Bisnis, 2025)
The population of this research is Butik Tumpeng catering customers, amounting to 150 people. The sample of this research is 60 respondents. The data collection technique for this study used a questionnaire/questionnaire which was tested for validation and reliability. Data processing in this study used SPSS (Statistic Package For the Social Sciences) version 28. The results of this study partially show that Service Quality and Perceived Value have a positive and significant effect on Customer Loyalty in the Butik Tumpeng catering in Depok City. The coefficient of determination is 65.6% and the remaining 34.4% is influenced by other variables not examined